Aplikasi sistem perhiasan 2in1 dengan tema Arabian Night - Ratu Fita Rahma Auliya'Ullah; Ellya Zulaikha; Ari Dwi Krisbianto (Institut Seni Indonesia Yogyakarta, 2020)
Jewelry in general is a fashion item that is favored because of its uniqueness, beauty, and ability to become one of the investment objects. Various types, materials, and models of jewelry can affect the value of the jewelry. One of them is gold jewelry. Gold jewelry is not only preferred because of the visual aesthetics of the style and model of the jewelery, but also because the weight of gram values in each design has a stable investment price, and can also be an identity that reflects the user's lifestyle and is the most considered factor when choosing jewelry. In the value of use, some jewelry has its own value for a culture and is often worn for traditional events or certain holidays, such as Eid or weddings. Innovations in jewelry designs are needed to produce new products that can meet market opportunities, one of which is multiform jewelry design, where one model of jewelry can be worn in two or more ways. This study focuses on jewelry with the concept of 2in1 which takes the theme of Arabian Night on the basis of cooperation with one of the largest gold companies in Indonesia to issue gold jewelery designs that will be produced and accepted by the public.Key words: jewelry, 2in1, investment, lifestyle, gold, market opportunities